SKIN DEEP: AN EXPLORATORY CASE STUDY OF THE ATTITUDE-BEHAVIOURAL GAP PHENOMENON AMONGST FEMALE MILLENNIALS IN THE CONTEXT OF THE SKINCARE INDUSTRY - Ransome, Natalie (The IIE, 2019)
The conventional skincare industry has been put in the spotlight regarding its negative impacts on the environment, animals as well as human health. As such, the harmful impacts of the skincare industry and the cosmetics industry as a whole, have given rise to the green movement. However, despite the rise of the green movement, there is a gap between consumers green purchasing intentions and decisions – this is referred to as the attitude-behavioural gap phenomenon (ABGP) which exists amongst female millennials in the context of the skincare industry. The findings of the study revealed that the main factor contributing to the ABGP is that female millennials are driven by self-interest. Therefore, the cost of having natural skincare products negatively affect their appearance, greatly outweighs any benefits. Furthermore, the findings indicated that female millennials distrust natural skincare products and perceive them to be inconvenient – these factors inhibit female millennials’ purchasing intentions. The findings of the study will provide marketers with possible interventions to shape consumers environmental attitudes towards the green skincare industry as well as influence their purchasing intentions. A focus group was used as this data collection method is useful for generating an in-depth understanding of participants’ experience and perceptions.
Keywords: Skincare industry; Millennials; Buying behaviour; Sustainable living; Green products; Green Movement